Environmental Sustainability in the Culture of Macroalgae, Oysters, and Low-Trophic Fish - Alves, Suellen Araujo; Santos, Michelle Roberta [UNESP]; Moraes-Valenti, Patricia [UNESP]; Sampaio, Dioniso Souza; Valenti, Wagner C. [UNESP] (MDPI, 2025)
Aquaculture plays a crucial role in meeting the needs of a growing human population and achieving the sustainable development goals outlined in Agenda 2030. However, it is essential that this sector grows sustainably. In this study, we hypothesized that environmental sustainability decreases as the trophic level of farmed species increases and that it is higher in integrated systems compared to monocultures. To test these hypotheses, we conducted a comparative analysis of the environmental sustainability indicators of some aquaculture systems, including the farming of primary producers, filter feeders, and low-trophic phagotrophs. We compiled secondary data on eighteen environmental sustainability indicators from seven aquaculture systems. Five are monocultures, including the farming of macroalgae (Hypnea pseudomusciformis), oysters (Crassostrea gazar) in a tropical environment, oysters in a subtropical environment, as well as tambatinga (hybrid Colossoma macropomum × Piaractus brachypomus) and tambaqui (Colossoma macropomum). Additionally, two are integrated systems: tambaqui raised in hapa nets (small cage-like enclosures) within Amazon river prawn (Macrobrachium amazonicum) ponds, and tambaqui and prawns cohabitating freely in the same ponds. A benchmark tool was utilized to establish reference values for comparing indicators between the systems, and a method was developed to create environmental sustainability indices that integrate all indicators. Environmental sustainability tends to decrease as trophic levels rise, supporting the initial hypothesis. However, the data revealed that Integrated Multi-Trophic Aquaculture (IMTA) systems ultimately have lower environmental sustainability than monocultures, which was contrary to our expectations. Algae and oyster farming were found to be more environmentally sustainable than low-trophic fish farming systems. Among these, the integrated systems did not demonstrate significantly greater sustainability than the monocultures, as initially anticipated. To gain a comprehensive understanding of sustainability, further research on the social and economic sustainability of these systems is necessary.
Keywords: benchmark; comparing indicator method; fish; macroalgae; oyster; sustainability indices; sustainable aquaculture